IDENTIFICATION OF GOLD MINERALIZATION ZONES USING TIME DOMAIN INDUCED POLARIZATION METHOD - Abdurrahman, Alwan
Gold is formed from a hot solution that comes from within the earth that comes from the surface through a crack or gap in the structure and then undergoes a rising process. The deposition that occurs in rock structures makes gold deposited in a scattered manner. Geophysical method that is often used in gold exploration is the induced polarization method. The research area is an area with epithermal gold deposit types. The presence of gold is associated with quartz minerals and sulfide minerals such as pyrite. This research uses time domain induced polarization method. Induced polarization method is appropriate because it can detect sulfide (pyrite) with high chargeability value well. Electrode configuration used is dipole-dipole with a spatial electrode of 25 m and n=6. There are eight lines, with seven lines having a total length of 400 m and one line having a total length of 800 m. The processing of the induced polarization data produces a 2D resistivity model with a value range of 0 – 800 m and a chargeability with a value range of 0 – 30 msec. The mineralized zone is thought to have medium – high resistivity (more than 50 ?m) and high chargeability (more than 20 msec) at points 400 to 700 in the middle of a North-South trending trajectory with an elevation of -20 to 50 m. When compared with the geological map, the mineralized zone is thought to occurs in Breccia-Tuff rocks which are intruded by Andesite lava. The mineralized zone is suspected to contain gold mineralization, although drilling is required to confirm gold mineralization.